If a + b + c = 0 and a b c = 0 , then find the value of a 2 b 2 + b 2 c 2 + c 2 a 2 a 4 + b 4 + c 4 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The answer can also be 0.
Log in to reply
If the answer is 0 it means that a=b=c =0 If this so then by putting the values the denominator becomes 0 and division by 0 is not possible.
As Tanveen points out, the expression cannot be equal to 0. In the worst case scenario, it is undefined.
I have edited the problem slightly for clarity.
We can Let a = 1 b = 1 and c = − 2
or a = 1 b = 2 and c = − 3
Means any a , b , c which on adding results to 0
during competitive exams this is the best way to do it [make sure your assumptions match the conditions given ]
Rearrange the first equation to get a = − ( b + c ) and substitue this into our given expression to get:
b 2 c 2 + ( b 2 + c 2 ) ( ( − ( b + c ) ) 2 ) ( − ( b + c ) ) 4 + b 4 + c 4
= b 2 c 2 + b 4 + 2 b 3 c + 2 b 2 c 2 + 2 b c 3 + c 4 2 b 4 + 4 b 3 c + 6 b 2 c 2 + 4 b c 3 + 2 c 4
= b 4 + 2 b 3 c + 3 b 2 c 2 + 2 b c 3 + c 4 2 ( b 4 + 2 b 3 c + 3 b 2 c 2 + 2 b c 3 + c 4 ) = 2
Problem Loading...
Note Loading...
Set Loading...
a 2 b 2 + b 2 c 2 + c 2 a 2 a 4 + b 4 + c 4 = a 2 b 2 + b 2 c 2 + c 2 a 2 ( a 2 + b 2 + c 2 ) 2 − 2 ( a 2 b 2 + b 2 c 2 + c 2 a 2 ) = a 2 b 2 + b 2 c 2 + c 2 a 2 [ ( a + b + c ) 2 − 2 ( a b + b c + c a ) ] 2 − 2 ( a 2 b 2 + b 2 c 2 + c 2 a 2 ) = a 2 b 2 + b 2 c 2 + c 2 a 2 4 ( a b + b c + c a ) 2 − 2 ( a 2 b 2 + b 2 c 2 + c 2 a 2 ) ∵ a + b + c = 0 = a 2 b 2 + b 2 c 2 + c 2 a 2 4 [ a 2 b 2 + b 2 c 2 + c 2 a 2 + 2 a b c ( a + b + c ) ] − 2 ( a 2 b 2 + b 2 c 2 + c 2 a 2 ) = 2